The current tax situation of occupational pensions and pan‐European pension funds - Mudrack, Gerhard (Journal of Business Economics and Management, 2007)
The main tax obstacle to the functioning of pan‐European pension funds is the exclusion from tax relief of cross‐border contributions. Many Member States have eliminated this obstacle or have announced that they will do this soon. The few Member States which may wish to continue the discrimination against foreign funds may find it very difficult to explain to the ECJ why they cannot do what so many other Member States already have. The conclusion of this article is, therefore, that for most situations, the main tax obstacle for pan‐European pension funds will be eliminated after the implementation date of the Pension Fund Directive, that was by 23 September 2005. The Pension Fund Directive includes the assumptions for a cross‐border activity of company pension funds. Among the existing national regulations of the setting of the systems of old age pensions the member states have to allow domestic companies in line with the Pension Fund Directive to be institution of foreign pension funds, which are licensed in other member states.First Published Online: 14 Oct 2010